Internet Web Communication Technology (WCT) and Information Communication Technology (ICT) development and use for veterinary medicine education in Nigeria (2000 -2009) (2010)
Internet web communication technology (WCT) usage in Nigeria has increased tremendously over the last decade. Veterinary education and practices in Nigeria have also profited largely from advances in internet WCT mainly, in last two decade. Veterinary Medicine Electronic Journals such as Access to Global Online Research in Agriculture (AGORA), African Journal Online (AJOL), and Health Information Network Access to Research Initiative (HINARI) are available free online. In particular, the (the official email group of the Nigerian Veterinary Medical Association NVMA), the interactive electronic mail communication network for members of the Nigerian Veterinary Medical Association (NVMA), has greatly stimulated Nigerian Veterinarians worldwide to active utilization of Internet WCT. The phenomenal increase in internet usage in education is attributable to massive collaborative support by such funding body as the MacArthur Foundation, working along other partners in the project “Partnership for Higher Education in Africa (PHEA)". Contrarily, the level of ICT use in Nigerian education system, including veterinary medicine education, is still very low, with an estimated 90% of Nigeria's educational institutions still at the emerging/infancy stage due to low funding, paucity of ICT infrastructure, irregular and low quality power supply and high cost of ownership of ICT facilities including the capital and operational costs. There is a pertinent need to focus research into and actively promote the usage of ICT in enhancing research and education in developing countries, with collaborative funding by International Organizations.